Comparison of two control groups for estimation of oral cholera vaccine effectiveness using a case-control study design. Issue 43 (13th October 2017) - Franke, Molly F.; Jerome, J. Gregory; Matias, Wilfredo R.; Ternier, Ralph; Hilaire, Isabelle J.; Harris, Jason B.; Ivers, Louise C.
Highlights: Effectiveness estimates using test-negative and matched community controls were similar. Test-negative controls may be a valid and efficient alternative to community controls. Non-null bias-indicator findings may not necessarily reflect bias in effectiveness estimates. Abstract: Background: Case-control studies to quantify oral cholera vaccine effectiveness (VE) often rely on neighbors without diarrhea as community controls. Test-negative controls can be easily recruited and may minimize bias due to differential health-seeking behavior and recall. We compared VE estimates derived from community and test-negative controls and conducted bias-indicator analyses to assess potential bias with community controls. Methods: From October 2012 through November 2016, patients with acute watery diarrhea were recruited from cholera treatment centers in rural Haiti. Cholera cases had a positive stool culture. Non-cholera diarrhea cases (test-negative controls and non-cholera diarrhea cases for bias-indicator analyses) had a negative culture and rapid test. Up to four community controls were matched to diarrhea cases by age group, time, and neighborhood. Results: Primary analyses included 181 cholera cases, 157 non-cholera diarrhea cases, 716 VE community controls and 625 bias-indicator community controls. VE for self-reported vaccination with two doses was consistent across the two control groups, with statistically significant VE estimates ranging from 72 to 74%. Sensitivity analyses revealed similar, though somewhat attenuated estimates for self-reported two dose VE. Bias-indicator estimates were consistently less than one, with VE estimates ranging from 19 to 43%, some of which were statistically significant. Conclusions: OCV estimates from case-control analyses using community and test-negative controls were similar. While bias-indicator analyses suggested possible over-estimation of VE estimates using community controls, test-negative analyses suggested this bias, if present, was minimal. Test-negative controls can be a valid low-cost and time-efficient alternative to community controls for OCV effectiveness estimation and may be especially relevant in emergency situations.